(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The staffing norms of the Quality Control Centers are currently regulated by Circular 08/2007/TTLT-BYT-BNV. Objective: Describe the current situation of the number of people working and the proportion of divisional and professional structure of the Quality Control Centers; compare the situation with the provisions of the Circular; analyze limitations in current regulations and propose policy solutions to ensure that the number of people working and the proportion of departmental and professional structure are suitable with the work characteristics of the Centers. Methods: Cross-sectional study, combining quantitative and qualitative research. Results: Most of the existing staff of the Centers are low compared to Circular 08/2007 regulations. The main human resources doing professional work at these Centers are pharmacists, medical technicians and engineers (biology, chemistry). The regulation thatnumber of people working at the Centers must be based on the province population size like the other Preventivecare centers and regulation on the structure of occupational titles is not suitable with the characteristics of the Quality Control Centers currently. Conclusion: To ensure the number of people working and the structure of professional titles at these Centers, it is necessary to define criteria that accurately reflect the workload (such as a number of samples) of the Centers, and to have specific regulations on the percentage of human resources with medical specialties such as pharmacists, medical technicians and other relevant occupational titles.